2018
DOI: 10.1021/acs.macromol.8b01449
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Topology Effects on Dynamics of Comb Polymer Melts

Abstract: Controlling polymer viscosity and flow is key to their many applications through strength and processability. The topology of the polymer i.e., linear, stars, and branched, affects the macroscopic flow characteristics of melts, where introducing one branch is sufficient to increase the viscosity significantly. While a number of studies have probed the effects of polymer topology on their rheology, the molecular understanding that underlies the macroscopic behavior remains an open question. The current study us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 49 publications
(93 reference statements)
0
20
0
Order By: Relevance
“…In the current paper, we investigate the transitions from comb to bottlebrush behavior; therefore, all of these variables are used for both topologies especially in the transition from comb to bottlebrush conformations. Substantial experimental [11,[29][30][31] and coarse-grained simulation works along with scaling analysis [24,25,[32][33][34][35] have been done to classify graft polymers into comb and bottlebrush classes with distinct rheological and mechanical properties. Substantial experimental [11,[29][30][31] and coarse-grained simulation works along with scaling analysis [24,25,[32][33][34][35] have been done to classify graft polymers into comb and bottlebrush classes with distinct rheological and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the current paper, we investigate the transitions from comb to bottlebrush behavior; therefore, all of these variables are used for both topologies especially in the transition from comb to bottlebrush conformations. Substantial experimental [11,[29][30][31] and coarse-grained simulation works along with scaling analysis [24,25,[32][33][34][35] have been done to classify graft polymers into comb and bottlebrush classes with distinct rheological and mechanical properties. Substantial experimental [11,[29][30][31] and coarse-grained simulation works along with scaling analysis [24,25,[32][33][34][35] have been done to classify graft polymers into comb and bottlebrush classes with distinct rheological and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…[24,25] Comb topologies have a backbone and side chains with an unperturbed random Gaussian conformation, while a densely grafted bottlebrush has a stretched backbone and side chains. However, both the shear and extensional viscosity increase exponentially [22,35,38,45] with the length of the entangled branches, which results in ultrahigh viscous materials with poor processing properties. Side chains were introduced on comb polymers to mainly control the rheological properties of polymers melt and solutions, especially the extensional viscosity and strain hardening behavior under extensional deformations, through variation of Z bb , Z sc , and q.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Once the short arm relaxes, the branch point takes a random hop along the confining tube. Wijesinghe et al [22] carried out molecular dynamics simulations for a coarse grained model for entangled polyethylene comb polymers. They showed that as the branch length increases, the combination of arm retraction and backbone mobility leads to a wide spectrum of arm relaxation times and that the motion of the polymer backbone is well described by repetition over intermediate time scales.…”
Section: Introductionmentioning
confidence: 99%